KERJASAMA RASULULLAH DENGAN NON-MUSLIM MEMBANGUN KESEJAHTERAAN UMAT - Rahayu, Sri Ulfa; Ginting, Ernawati Br (UIN Sumatera Utara Medan, 2019)
Today, Muslim are often seen as radical and intolerant people against followers of other religious who are suspected of being terrorist. This triggers conflict between people to cause casualties. It even happened when named Muhammad, he could not go to the west. This is different from the messenger of Allah, who was also an apostle and leader in Makkah and Madinah, but was successful in building people’s welfare from a social and economic perspective. The method of this writing is descriptive qualitative method, namely the writing process with a methodology that investigates phenomena and social situations. The type of writing according to the place is research library with a historical study with an approach to revelation from the Koran and Hadith. The purpose of this paper is the extent of the prophet’s cooperation at that time so that the people prospered and for Muslims now to follow the way of the Prophet who was full of tenderness. The results of this paper are that the Messenger of Allah is a person who is very tolerant to other religious, gentle and has never forcibly spread Islam to non-Muslims. He also collabored with non-Muslims in terms of government, namely diplomatic relations and trade relations, namely the Prophet once pawned his armor to Jews.